2017
DOI: 10.1037/prj0000244
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing intensive targeted computerized cognitive training with social cognitive exercises for people with schizophrenia: An interim report.

Abstract: Objective Individuals with schizophrenia demonstrate cognitive, social cognitive and motivational deficits that contribute to impairment in real-world functioning. In the current study, we investigated the effects of supplementing computerized neurocognitive training with social cognitive exercises, as compared to neurocognitive training alone. Methods In this ongoing, double-blind, randomized controlled trial of 111 participants with psychosis, we compare the effects of supplementing intensive targeted cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 72 publications
6
39
2
Order By: Relevance
“…A similar study by Fisher et al evaluated targeted cognitive training, specifically auditory and visual processing training and CSCT compared with targeted cognitive training alone. 44 These authors did not find that a combined intervention demonstrated significantly more improvement in most domains of cognition and functioning, although they did find that combined training resulted in greater improvements in reward processing, specifically increased consummatory and anticipatory pleasure, which have been linked to motivated and goal-directed behavior, as well as prosody identification. This was significant because of past findings suggesting that the relationship between social cognition and social functioning is mediated by the level of motivation, with more support for the theory that poor socialcognitive abilities impeded motivation, leading to poor functioning.…”
Section: Training Interventions Aimed At Cognition and Social Cognitionmentioning
confidence: 95%
“…A similar study by Fisher et al evaluated targeted cognitive training, specifically auditory and visual processing training and CSCT compared with targeted cognitive training alone. 44 These authors did not find that a combined intervention demonstrated significantly more improvement in most domains of cognition and functioning, although they did find that combined training resulted in greater improvements in reward processing, specifically increased consummatory and anticipatory pleasure, which have been linked to motivated and goal-directed behavior, as well as prosody identification. This was significant because of past findings suggesting that the relationship between social cognition and social functioning is mediated by the level of motivation, with more support for the theory that poor socialcognitive abilities impeded motivation, leading to poor functioning.…”
Section: Training Interventions Aimed At Cognition and Social Cognitionmentioning
confidence: 95%
“…Several recent studies have looked at effects of remediation on social reward processing in schizophrenia [73,74]. Vinogradov and colleagues paired computerized social cognitive training with "cold" cognitive training [73,74] because of previous studies suggesting that poor social cognitive abilities may impede motivation and lead to poor functioning [73].…”
Section: Reward Learning In Schizophreniamentioning
confidence: 99%
“…Several recent studies have looked at effects of remediation on social reward processing in schizophrenia [73,74]. Vinogradov and colleagues paired computerized social cognitive training with "cold" cognitive training [73,74] because of previous studies suggesting that poor social cognitive abilities may impede motivation and lead to poor functioning [73]. Greater improvements in both cold cognition (e.g., prosody identification) and self-reported reward processing were found following the combined treatment than following cognitive treatment alone [73] which were sustained at six-month follow up [74].…”
Section: Reward Learning In Schizophreniamentioning
confidence: 99%
“…Results from the pilot study indicated significant improvements on prosody identification, facial memory, social functioning, motivation and reward sensitivity ( Nahum et al, 2014 ). More recently, a randomized controlled trial found that supplementing CT with these social cognitive exercises in people with psychotic disorders confers greater benefits in prosody identification and reward processing relative to CT alone( Fisher et al, 2017 ). While preliminary evidence indicates that CT is efficacious, access to and engagement with CT by individuals with SZ remain outstanding challenges.…”
Section: Introductionmentioning
confidence: 99%